How do cultural activities influence happiness? Investigating the relationship between self-reported well-being and leisure - Ateca-Amestoy, Victoria; Gerstenblüth, Mariana; Mussio, Irene; Rossi, Máximo (Estudios Económicos de El Colegio de México, 2016)
Leisure is a human condition related to the discretionary use of time in a rewarding way that contributes to individual well-being. Individuals decide to engage on cultural activities to enjoy pleasant experiences. Cultural participation can be explained in different dimension, considering how the individual access those cultural experiences: by live attendance, by home consumption, by community practice. We find that the magnitude of the positive effect of cultural activities on the top happiness goes in this descending order: cinema going, participating in cultural events, listening to music, reading books and watching TV.